HUMAN RIGHTS AND LAW ENFORCEMENT - Eleanora, Fransiska Novita; Sari, Andang (Lambung Mangkurat Law Journal, 2019)
Humans born into the world have declared their rights and natural rights as gifts from the Almighty, God and every State must recognize them as legal subjects who must always be respected and protected to realize human values ​​well. Therefore; no one can or can act negatively, including the state or even the authorities or the government. Conceptually, a country that is expected to realize it is only a legal state that is considered legitimate and adheres to the notion of democracy, namely democracy will become a rule and law. The realization of the rule of law is to take action against perpetrators who are proven to have committed crimes and human rights violations. This paper explains that there are still many cases of gross violations of human rights that have not been clearly revealed and the perpetrators have not been given appropriate punishment, by giving sanctions to the perpetrators, so that law enforcement is not realized. The embodiment of the rule of law is that it can capture cases of gross violators of human rights and convict the perpetrators in accordance with the laws that apply in accordance with the characteristics of the rule of law. The problem is whether law enforcement has been realized especially in human rights violations and can be resolved through negotiation, conciliation and mediation.